Evaluator of 2 Programs of Tertiary Education - Georgiades, Tasos (My University, 2026)
Member of a Visiting Team of Experts in Evaluating 2 Programs of Tertiary Education, Council of Education Evaluation–Accreditation, Ministry of Education and Culture